Unmet goals of neonatal nursing - an observational study - Deshabhotla, Saikiran; Sandeep, Sonnathi; Tandur, Baswaraj (International Journal of Contemporary Pediatrics, 2020)
Background: Neonatal nurses are the backbone of any neonatal service, spending maximum time in the care of the sick New-borns in the Neonatal intensive care unit (NICU). Objective of the study was to know about the educational qualification and assess the self-reported confidence in various clinical skills among the nurses working in level 2 & 3 NICUs, preferred learning methodology and assess self-reported stressors among the nurses working in level 2 and level 3 NICUs Methods: This cross-sectional study was done across Level II and Level III Neonatal intensive care units in urban areas of the city of Hyderabad, India over one year from January 2019 to December 2019. Individual questionnaires were distributed to each registered nurse working in the NICU for a minimum duration of six months who were willing to participate. Results: A total of 217 respondents were enrolled. The majority of the nurses were having General Nursing and Midwifery (GNM) qualification 52% (n=112). Nearly 26% (n=58) of the nurses were not comfortable performing bag and mask ventilation. Learning from senior nurses/colleagues as the most preferred mode of learning 45% (n=98). Low salaries 45% (n=98) followed by absence of doctors in emergency situations 37% (n=81) and high documentation (paperwork) 36% (n=78) were most frequently reported stressors. Conclusions: Most of the nursing participants qualified as GNM. Lacking skills of neonatal resuscitation. Mentor based learning needs to be facilitated by raising a cadre of neonatal nursing tutors in various nursing colleges. Paperless monitoring systems and other automation methods should be developed to reduce the documentation work of the staff.